URGENSI SUNAH DALAM PENETAPAN HUKUM ISLAM - FAUZIYAH, RIRIN (Universitas Nahdlatul Ulama Sunan Giri, 2018)
“Sunnah as one of the sources of Islamic law that occupies the second position after al-Qur'an, it is still a matter of disputed. The dispute stems from differences of opinion about the legal force contained in the sunnah, which includes binding and has the power to emulate or not. These differences of opinion have different legal consequences. The position and urgency of sunnah in the formation of Islamic law also did not escape from the dispute. Some scholars believe that the sunnah as the second source of law is capable of independently establishing the law, but some others assume that the sunnah is not a source of law-settlers but rather the explanation and detailing, so that anything born from sunnah has actually been covered in al-Qur'an 'an. Sunnah serves to explain and strengthen the laws that already exist in al-Qur'an. Sunnah also provides the details and interpretations of the verses of al-Qur'an that are still mujmal or global, providing limits on the things that have not been limited, giving specificity (takhsis) on the verses that are general, and provide explanations of things which is still complicated in al-Qur'an. Sunnah also serves as the forming of a new law that does not exist in al-Qur'an.”